Analisis perbandingan antara pemikiran Ibn 'Abd al-Salam (M660H) dan al-Shatibi (M790H) tentang teori bid'ah / Syed Mohd Jeffri Syed Jaafar - Syed Mohd Jeffri, Syed Jaafar (2017)
The issue of bid‘ah has been a polemic subject among muslim scholars for a long time. It is largely attributed by the differences of their perception about the terminology of bid‘ah itself. There are two conflicting streams in response to the concept of bid‘ah. Among the pioneers of the two streams are Ibn ‘Abd al-Salam (M660H) and al-Shatibi (M790H). Coming a century after Ibn ‘Abd al-Salam, it gives al-Shatibi the opportunity to debate openly and criticize the theory stated by Ibn ‘Abd al-Salam as well as other groups that divided heresy into two; hasanah and dalalah. This thesis aims to comparatively study thoughts of Ibn ‘Abd al-Salam (D660H) and al-Shatibi (D790H) on the theory of bid‘ah within the development of Islamic law based on the framework at early times of Islam. This qualitative study uses the library methodology completely as the data collection process, and the data analysis process is carried out through the methods of inductive, deductive and comparative. The study found that the life background of both scholars had influenced their thoughts on the concept of bid‘ah. The study also found the differences in the interpretation of texts related to the theory of bid‘ah also engendered the perceptions that contradict toward each other. This conflict also resulted in a big impact on Muslim unity, creating discord and confusion in understanding the Islamic law. The study also concludes that a theory developed by Ibn ‘Abd al-Salam is more suitable with the reality in Malaysia based on the development of Islamic law and the framework at early times of Islam. In harmonizing these two views, each proponents of both schools should recognize the things agreed and disagreed upon the matters in relation to the theory of bid‘ah. As for the things that are unanimously agreed on its digression, it must totally be rejected among the scholars while for the disputed matters, they should discuss with courtesy and full of ethics so that at the end of that discussion, they will make the best solution for ummah.